Prevalence of Multidrug-Resistant Salmonella in Raw Salad Vegetables in Dhaka Metropolitan Area - Sarker, Palash Kumar; Rahman, Hafizur; Ara, Kulsum; Kabir, Md Shahidul; Pramanik, Shishir Kanti; Hasan, Maruf (MIST International Journal of Science and Technology, 2023)
Raw salad vegetables have become very popular among consumers due to their multiple health benefits. The bacteriological quality of these salad vegetables is of great public health concern. This study was conducted to determine the presence of potential pathogenic and multidrug-resistant (MDR) bacteria in raw salad vegetables served in different restaurants in Dhaka, the capital city of Bangladesh. A total of 50 samples, comprising different types of raw salad vegetables were collected from restaurants in Mirpur (n=10), Dhanmondi (n=10), Old Dhaka (n=10), Gulshan (n=10) and Bashundhara Residential Area (n=10). The highest counts for total coliforms and fecal coliforms were 4.02 × 103 cfu/ml and 1.3×103 cfu/ml, respectively. The isolates were E. coli, total coliform, fecal coliform and Salmonella spp. Among them, fecal coliform and Salmonella spp. were found to be more pathogenic. As potential pathogenic bacteria, Salmonella spp. were tested for antibiotic sensitivity and all of them showed resistance against amoxicillin, ampicillin, azithromycin, chloramphenicol, ciprofloxacin, erythromycin, kanamycin, streptomycin, tetracycline, norfloxacin, and trimethoprim. The findings assist to understand the level of contamination of pathogenic and MDR bacteria in raw salad vegetables, which will create awareness of food safety and public health. MIJST, Vol. 11, June 2023 : 51-57 DOI: https://doi.org/10.47981/j.mijst.11(01)2023.396(51-57)